Analisis Performa Kompor Bertekanan Menggunakan Bahan Bakar Minyak Pirolisis Dan Minyak Tanah - Rasmin, Rasyid; Sudia, Budiman; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2020)
The scarcity of fuel oil (BBM) that occurs due to the limited amountr. Therefore, alternative energy is needed to overcome these problems, one of which is the use of plastic pyrolysis oil on pressure cookers ini the household sector among the lower class of society. The purpose of this study was to determine the performance of a pressurized stove using pyrolysis oil and kerosene as fuel. The method used in this research is an experimental method by making pyrolysis oil and mixing kerosene, taking personal data directly with several variations of the mixture. The results of the research on the performance of a pressurized stove by heating 2.5 liters of water show that the most efficient use of fuel ini a mixture of 80% kerosene and 20% pyrolysis oil produces the highenst average temperature of 349 degrees Celcius, maximum flame height of 26 cm, the fastest water boiling time is 10:46 minutes by using at least 130 ml of fuel.Key words: Alternative fuel, pyrolysis, kerosene, performance